Perforation model of thin rock slab subjected to rigid projectile impact at an intermediate velocity. (May 2020) - Xing, H.Z.; Zhao, J.; Wu, G.; Ruan, D.; Dehkhoda, S.; Lu, G.X.; Zhang, Q.B.
Abstract: Intermediate-velocity projectile impact can cause considerably mass damage on a slab of geomaterials since most of the kinetic energy of the projectile was left in the target during perforation. The effect of scabbing preliminarily reduces the effective thickness of slab making the intermediate-velocity impact much more energy-effective in perforation. In this study, 24 shots were conducted on thin slabs of sandstone with three nose-shape projectiles (i.e., flat, hemispherical, and conical) at velocities ranging from 120 to 403 m/s by a one-stage gas gun. Two high-speed cameras were used to establish the stereovision of the rear face of the target at 200, 000 frames per second (fps). The volume and velocity of ejected fragments from the rear face were obtained by the three-dimensional digital image correlation (3D-DIC) technique. A side-view high-speed camera was applied to capture the deceleration of projectile to calibrate the constants in the penetration model at a frame rate of 380, 000 fps. A variation could be over 10% in predicting the depth of penetration (DOP) with calibrated and uncalibrated parameters. The equations of perforation limit, ballistic limit and residual velocity for intermediate-velocity perforation models are proposed, respectively. The results show that the minimum velocity required to perforate a thin slab by intermediate-velocity perforation model is 71% less than that required in high-velocity perforation.